Perilaku Seksual Melalui Media Phone Sex - MAULIDA, ISNINA, Dr. Nisa Rchmah N.A., M.Si., Psi (2016)
This study aims to find, understand and describe sexual behavior through media phone sex and the reasons underlying it. Informants in this study had karakteristis namely a) do not phone sex with the couple. b) sexual behavior through media phone sex at least more than one year. Selection of informants was purposively snowballing sampling, that the selection of informants was based on information from informants that three informants male and one female informant. Belakanginforman background is from a variety of different states, namely teachers, artists and students. The reason informants did phone sex was as lonely and curious. Idilakukan Phone sex with a girlfriend and close friends. The method in this research is qualitative phenomenology is the categorization of the themes that emerged and discussion of research results. The results of these studies show that sexual behavior through media phone sex is a conversation about sex performed by a minimum of two people, the reasons that people do phone sex because of curiosity and loneliness and the impact of phone sex is declining academic value, the value of religious, a person becomes easier anger, loss of concentration, loss of the spirit if not do phone sex and can lead to addiction. As for phone sex do informant to plan early sexual intercourse directly.